Visible-light-driven BiOI and GO/BiOI photocatalysts for organic pollutants degradation and hydrogen production using low power sources - Oros-Ruiz, Socorro; Ojeda-Galván, Hiram Joazet; Quintana, Mildred; Leyva-Ramos, Roberto; Moral-Rodríguez, Adriana Isabel; Mendoza-Mendoza, Esmeralda (Frontiers in Nanotechnology, 2024)
BiOI and (3 wt.%)GO/BiOI visible-light-driven photocatalysts were obtained by a one-pot solvothermal method and successfully applied to the degradation of single and binary dye solutions of rhodamine B (RhB) and methylene blue (MB) and H2 production using very low-power sources. The GO/BiOI with hierarchical flower morphologies exhibited the highest activity, achieving RhB and MB photodegradation percentages (%Xdye) of 100 and 80%, respectively, in 240 min employing a simple 19 W white LED array. Furthermore, GO/BiOI dosage and RhB initial concentration play an essential role in dye degradation, and scavenger assays confirmed that holes and superoxides are the main species causing RhB oxidation. TOC analysis determined an efficiency of 70%, and after three uses, the GO/BiOI attained a %XRhB of 84%. The H2 evolution was performed under 2 W UV light, yielding 323.25 µmol/h•g of H2 for BiOI, and the addition of GO nanosheets increased the photoactivity of GO/BiOI up to 63% (509.61 µmol/h•g). The catalytic activity of GO/BiOI is superior to values reported in the literature considering nominal power consumption (kWh) vs. efficiency of RhB degradation or H2 production.